Active Media Technology 6th International Conference, AMT 2010, Toronto, Canada, August 28-30, 2010. Proceedings - An, Aijun; Lingras, Pawan; Petty, Sheila; Huang, Runhe; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
This book constitutes the refereed proceedings of the 6th International Conference on Active Media Technology, AMT 2010, held in Toronto, Canada, in August 2010. The 52 revised full papers and 2 invited talks were carefully reviewed and selected for inclusion of the book. They are grouped in topcial sections on active computer systems and intelligent interfaces; adaptive Web sysetms and information foraging agents; AMT for semantic Web and Web 2.0; data mining, ontology mining and Web reasoning; e-commerce and Web services; entertainment and social applications of active media; evaluation of active media and AMT based systems; intelligent information retrieval; machine learning and human-centered robotics; multi-agent systems; multi-modal processing, detection, recognition, and expression analysis; semantic computing for active media and AMT-based systems; smart digital media; Web-based social networks; and Web mining, wisdom Web and Web intelligence.
Keynote Talks -- Technology-Mediated Social Participation: Deep Science and Extreme Technology -- Active Smart u-Things and Cyber Individuals -- Active Computer Systems and Intelligent Interfaces -- A Case for Content Distribution in Peer-to-Peer Networks -- Interactive Visualization System for DES -- Intelligent Implicit Interface for Wearable Items Suggestion -- Adaptive Web Systems and Information Foraging Agents -- Folksonomy-Based Ontological User Interest Profile Modeling and Its Application in Personalized Search -- Visualizing Threaded Conversation Networks: Mining Message Boards and Email Lists for Actionable Insights -- AMT for Semantic Web and Web 2.0 -- A Spatio-temporal Framework for Related Topic Search in Micro-Blogging -- Exploiting Semantic Hierarchies for Flickr Group -- Understanding a Celebrity with His Salient Events -- User Interests: Definition, Vocabulary, and Utilization in Unifying Search and Reasoning -- Ontology Matching Method for Efficient Metadata Integration -- Data Mining, Ontology Mining and Web Reasoning -- Multiagent Based Large Data Clustering Scheme for Data Mining Applications -- Fractal Based Video Shot Cut/Fade Detection and Classification -- Performance Evaluation of Constraints in Graph-Based Semi-supervised Clustering -- Analysis of Research Keys as Tempral Patterns of Technical Term Usages in Bibliographical Data -- Natural Language Query Processing for Life Science Knowledge -- E-Commerce and Web Services -- A Semantic Web Services Discovery Algorithm Based on QoS Ontology -- Implementation of an Intelligent Product Recommender System in an e-Store -- Recommendation of Little Known Good Travel Destinations Using Word-of-Mouth Information on the Web -- Entertainment and Social Applications of Active Media -- The Influence of Ubiquity on Screen-Based Interfaces -- Perception of Parameter Variations in Linear Fractal Images -- Music Information Retrieval with Temporal Features and Timbre -- Evaluation of Active Media and AMT Based Systems -- Towards Microeconomic Resources Allocation in Overlay Networks -- Investigating Perceptions of a Location-Based Annotation System -- Apollon13: A Training System for Emergency Situations in a Piano Performance -- Intelligent Information Retrieval -- Exploring Social Annotation Tags to Enhance Information Retrieval Performance -- A Hybrid Chinese Information Retrieval Model -- Term Frequency Quantization for Compressing an Inverted Index -- Chinese Question Retrieval System Using Dependency Information -- Machine Learning and Human-Centered Robotics -- A Novel Automatic Lip Reading Method Based on Polynomial Fitting -- An Approach for the Design of Self-conscious Agent for Robotics -- K-Means Clustering as a Speciation Mechanism within an Individual-Based Evolving Predator-Prey Ecosystem Simulation -- Improving Reinforcement Learning Agents Using Genetic Algorithms -- Robust and Efficient Change Detection Algorithm -- Multi-Agent Systems -- Building Users$1 (BProfiles from Clustering Resources in Collaborative Tagging Systems -- Some Optimizations in Maximal Clique Based Distributed Coalition Formation for Collaborative Multi-Agent Systems -- Multi-Modal Processing, Detection, Recognition, and Expression Analysis -- Enhanced Intra Coding of H.264/AVC Advanced Video Coding Standard with Adaptive Number of Modes -- Extracting Protein Sub-cellular Localizations from Literature -- Semantic Computing for Active Media and AMT Based Systems -- Enhancing Content-Based Image Retrieval Using Machine Learning Techniques -- Modeling User Knowledge from Queries: Introducing a Metric for Knowledge -- Computer-Assisted Interviewing with Active Questionnaires -- Smart Digital Media -- Assessing End-User Programming for a Graphics Development Environment -- Visual Image Browsing and Exploration (Vibe): User Evaluations of Image Search Tasks -- Web Based Social Networks -- Contextual Recommendation of Social Updates, a Tag-Based Framework -- Semantic Web Portal: A Platform for Better Browsing and Visualizing Semantic Data -- NicoScene: Video Scene Search by Keywords Based on Social Annotation -- Web Mining, Wisdom Web and Web Intelligence -- Social Relation Based Search Refinement: Let Your Friends Help You! -- An Empirical Approach for Opinion Detection Using Significant Sentences -- Extracting Concerns and Reports on Crimes in Blogs -- Automatically Extracting Web Data Records -- Web User Browse Behavior Characteristic Analysis Based on a BC Tree -- Clustering Web Users Based on Browsing Behavior -- Privacy Preserving in Personalized Mobile Marketing.s
Keywords: Computer science; Computer Communication Networks; Database management; Data mining; Information systems; Artificial intelligence; Computer Science; Information Systems Applications (incl.Internet).; Artificial Intelligence (incl. Robotics).; Computer Communication Networks; Database Management; User Interfaces and Human Computer Interaction; Data Mining and Knowledge Discovery